Utilization of PhET Media in Understanding the Concept of Electrical Circuits of Elementary School Students: A Literature Review - Adilla Dzakiroh; Annisa Haniifah; Della Rosa; Ratna Khoerunisa; Neni Maulidah (Indonesian Journal of Primary Education, 2024)
This research aims to examine the use of PhET Interactive Simulation media in helping students facilitate understanding of the concept of electrical circuit material for elementary school students, through a qualitative approach based on Systematic Literature Review (SLR). The method used is a literature review by sharing and disseminating various scientific articles, books and relevant reference sources, various research related to certain topics in a structured manner. The results of the analysis show that from 13 articles that explain electrical circuit material at elementary school level, it can be seen that the use of Physics Education Technology (PhET) Simulation media has proven to be effective in helping construct conceptual understanding for elementary school students, especially in electrical circuit material because PhET Simulation has advantages such as tools. Virtual learning is economical, easy to access and interactive so that it makes them more interested and active in learning and can overcome time constraints, overcome limited resources thereby increasing effectiveness in the practical learning process. PhET Simulation Media can support students in understanding concepts better through interactive and interesting simulations, while providing opportunities for them to build knowledge independently through easy-to-access virtual laboratories. Thus, the use of PhET Simulation media has a significant positive impact on the development of students' cognitive understanding in the learning process.